Media Device Use and Vision Disorders in the Pediatric Age: The State of the Art - Elena Bozzola; Mariangela Irrera; Romie Hellmann; Salvatore Crugliano; Michele Fortunato (MDPI AG, 2024)
Introduction. Evidence is consistent with increased screen viewing time among children and adolescents, and anticipation at the age at which children interact with media devices. Incorrect use of technology, as well as overuse, may lead to serious consequences. This study aims to revise scientific international literature and to describe the potential eye risks correlated to screen viewing time in the pediatric age. Materials and Methods. A review of the literature was performed according to the PRISMA 2020 guidelines, using the search terms "media device" and "eye" with the filter "age 0-18". Results. Analyzing the international literature, we found 26 articles. Pre-myopia, myopia, digital eye strain, and acute acquired comitant esotropia were listed as potential and time-related consequences associated with the incorrect use of media devices among children and adolescents. Discussion. Family education on media device exposure and potential risk for children and adolescents' sight in case of prolonged digital/screen exposure is required. During pediatric check controls, a dialogue with families on prolonged media device use at a close distance should be undertaken. Pediatricians and ophthalmologists should consider screen viewing time in case of ocular problems.